Die Rol van Bemarking in die Kerk - North, E. J. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2004)
The main aim of this article is to present a theoretical overview of the nature and scope of marketing and to reflect on the use and application thereof for the church. Although the church is considered to be a non-profit organisation, it is challenged to render services of a high quality that will add value to and improve the standard of living to every one with whom the church interacts. Specific emphasis is placed on the marketing of services and the role of customer relationship in this regard. References to a marketing research project undertaken in a religious context in South Africa underlines the necessity of the church to take cognisance of the value of marketing for the church.